“OPPA SCAM” AND ROMANTIC RELATIONSHIPS IN K-DRAMAS: IDOLATRY AND FAN ACTIVISM IN BRAZIL - Lemos, Ligia Prezia; Pinheiro, Mariana Marques de Lima (Brazilian Creative Industries Journal, 2024)
The research addresses the reception of K-dramas by Brazilian fandom in terms of transculturality, in which fans from Brazil play a fundamental role in the dialogue about, promotion and sharing of content related to both actors and characters. From there, it explores issues of representation and gender roles. Based on previous research findings, it uses qualitative methods, without seeking generalizations, but highlighting aspects related to fan idolatry and activism. It focuses on analyzing issues related to masculinity and the idealization of South Korean men in K-dramas, which can lead to the dissociation between fiction and reality. This dissociation is exemplified by the “oppa scam”, in which people pretend to be South Korean actors to extort money from Brazilian fans. It concludes that Brazilian fans are inserted in a global and local environment that can generate unexpected situations regarding the assimilation of pop culture in specific contexts.